The effects of employees' perceptions of competency models on employability outcomes and organizational citizenship behavior and the moderating role of social exchange in this effect - (:unkn) unknown (ELSEVIER SCIENCE BV, 2014)
Competencies of human resource, which are considered as factors creating innovation and value to organizations, are becoming extremely important for organizations. An understanding of competency-based development will improve employees' performance and therefore will help to improve the performance of the organization. Our research was conducted in Istanbul by using convenient sampling method on 175 participants working in banking, telecommunications, health care, aeronautical and food industries. According to the results of the research, employees' perceptions regarding the relevance and fairness of competency models have a positive effect on employability outcomes and organizational citizenship behavior. It has been concluded that social exchange has a moderating role on this positive effect. (C) 2014 Published by Elsevier Ltd.
Keywords: Competency models; social exchange; employability orientation and employability activities; organizational citizenship behavior; WORK; MANAGEMENT; SUPPORT